Nucleoside phosphonic acids in thymidine phosphorylase inhibition: structure-activity relationship - Panova, Natalya; Kosiová, Ivana; Petrová, Magdalena; Vanĕk, Václav; Liboska, Radek; Kovacková, Sona; Kocalka, Petr; Králíková, Sárka; Tocík, Zdenĕk; Páv, Ondrej; Paces, Ondrej; Rejman, Dominik; et al. (Nucleic acids symposium series, 2008)
A number of structurally diverse nucleoside phosphonic acids have been tested against human recombinant thymidine phosphorylase and human platelets supernatant using 2'-deoxy-5-nitrouridine as the substrate. We have selected several inhibitors working at micromolar level as lead structures for further evaluation.
Keywords: CHO Cells; CHO buňky; křečci praví; Enzyme Inhibitors; Nucleosides; zvířata; Phosphorous Acids; inhibitory enzymů; Thymidine Phosphorylase; nukleosidy; Animals; lidé; Blood Platelets; Cricetinae; Cricetulus; thymidinfosforylasa; Humans; kyseliny fosforité; Structure-Activity Relationship; trombocyty; vztahy mezi strukturou a aktivitou